Pengaruh Disiplin Kerja, Sikap Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan PT. Nusa Jaya Farma Indonesia (Nufarindo) Semarang - Edi Kurniawan; Ida Martini Alriani (Jurnal Ekonomi Manajemen Akuntansi, 2022)
The purpose of this study was to determine the effect of work discipline, work attitude and job satisfaction on employee performance at PT. Nusa Jaya Farma Indonesia. The population of this study are employees of PT. Nusa Jaya Farma Indonesia, which has a total of 778 employees. The samples were taken using a random sampling technique, namely a number of 89 respondents. This research data analysis tool uses multiple linear regression. The results showed that job satisfaction has a positive effect on employee performance. This is shown by the value of t count is greater than t table, namely 2.246 > 1.664 with a sig value smaller than alpha, namely 0.027 <0.05, so it is significant. The regression coefficient of work discipline (β1) has a positive sign of 0.211 which means that the better the work discipline, the higher the employee performance. Work attitude has a positive effect on employee performance. This is shown by the value of t count is greater than t table, namely 3.239 > 1.664 with a sig value smaller than alpha, namely 0.002 <0.05, so it is significant. The work attitude regression coefficient (β2) is positive at 0.302 which means that the higher the work attitude, the higher the employee's performance. Work discipline has a positive effect on employee performance. This is shown by the value of t count is greater than t table, namely 3.151 > 1.664 with a sig value smaller than alpha, namely 0.002 <0.05, so it is significant. The regression coefficient of job satisfaction (β3) is positive at 0.316 which means that the higher the job satisfaction, the higher the employee performance.